Longitudinal study of six seasons of match injuries in elite female rugby union - Starling, L. T.; Gabb, N.; Williams, S.; Kemp, S.; Stokes, K. A. (British Journal of Sports Medicine, 2023)
Objective: To establish match injury rates and patterns in elite female rugby union players in England.